THE ROLE OF MANAGEMENT IN THE DEVELOPMENT OF SPORTS (International Scientific Journal Alfraganus, 2026)
The processes of deep changes, consistent reform and liberalization of all aspects ofpolitical and socio-economic life, democratic renewal and modernization of our society aredeveloping rapidly in our country. In this regard, the huge tasks defined and consistentlyimplemented in the way of forming a strong civil society are creating a solid foundation.
Keywords: Factor, sports management, sports organizations, sports, conditions, sports management objects, sports management subjects, sports, children's sports, national sports, national games, big sports, Olympics, Olympic Games, sports facilities.